2013
DOI: 10.1016/j.anbehav.2012.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Facial markings in the hover wasps: quality signals and familiar recognition cues in two species of Stenogastrinae

Abstract: Keywords:animal communication badge of status conventional signal dominance hierarchy hover wasp Liostenogaster flavolineata Liostenogaster vechti quality signal recognition system social behaviour Both recognition and conventional signals are widespread in the animal kingdom. Chemical communication plays a major role in invertebrates, and especially in social insects. In the last decade, observational and experimental evidence has shown the existence of visual quality signals and individual recognition cues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
0
30
1
Order By: Relevance
“…A pioneering experiment demonstrated that males of the stenogastrinae wasp Parischnogaster mellyi use a visual status badge during flying duels for winning a perch in aerial leks [14]. It was since found that visual communication plays a key role in the social interactions between colony members and indeed, a facial badge of status has been shown to convey information on the agonistic qualities in foundresses of the North American population of Polistes dominula and to regulate dominance hierarchies in the stenogastrinae wasp Liostenogaster vechti [10,11], but see [15,16]. Polistes fuscatus wasps are more aggressive to individuals with unfamiliar appearances landing on the nest [9] and they are able to remember the individual identity of partners after one week of interactions with several other wasps [17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A pioneering experiment demonstrated that males of the stenogastrinae wasp Parischnogaster mellyi use a visual status badge during flying duels for winning a perch in aerial leks [14]. It was since found that visual communication plays a key role in the social interactions between colony members and indeed, a facial badge of status has been shown to convey information on the agonistic qualities in foundresses of the North American population of Polistes dominula and to regulate dominance hierarchies in the stenogastrinae wasp Liostenogaster vechti [10,11], but see [15,16]. Polistes fuscatus wasps are more aggressive to individuals with unfamiliar appearances landing on the nest [9] and they are able to remember the individual identity of partners after one week of interactions with several other wasps [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cuticular hydrocarbons (hereafter CHCs) together with pheromones are assumed to regulate almost all social interactions, implying the chemical senses as the predominant channels of communication in insect societies [6,8]. In the last two decades, however, visual communication abilities have been discovered in two subfamilies of social wasps [9][10][11][12][13]. A pioneering experiment demonstrated that males of the stenogastrinae wasp Parischnogaster mellyi use a visual status badge during flying duels for winning a perch in aerial leks [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that the markings are involved in intra-specific communication, as contrasting markings are known to be used for this purpose in other Hymenoptera. For example, social Vespidae use individual markings for kin recognition (Baracchi et al 2013) or minimization of conflict costs (Tibbets & Lindsay 2008). Even though they are taxonomically distantly related, from a functional perspective many lepidopterans exhibit "white" surfaces reflecting UV flashes, hence favoring mate location (Brunton & Majerus 1995).…”
Section: Discussionmentioning
confidence: 99%